Lead-Induced Atypical Parkinsonism in Rats: Behavioral, Electrophysiological, and Neurochemical Evidence for a Role of Noradrenaline Depletion - Sabbar, Mariam; Delaville, Claire; De Deurwaerdère, Philippe; Lakhdar-Ghazal, Nouria; Benazzouz, Abdelhamid (Frontiers in Neuroscience, 2018)
Background: Lead neurotoxicity is a major health problem known as a risk factor for neurodegenerative diseases, including the manifestation of parkinsonism-like disorder. While lead is known to preferentially accumulate in basal ganglia, the mechanisms underlying behavioural disorders remain unknown. Here, we investigated the neurophysiological and biochemical correlates of motor deficits induced by sub-chronic injections of lead. Methods: Sprague Dawely rats were exposed to sub-chronic injections of lead (10 mg/kg, i.p.) or to a single i.p. injection of 50 mg/kg N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine hydrochloride (DSP-4), a drug known to induce selective depletion of noradrenaline. Rats were submitted to a battery of behavioural tests, including the open field for locomotor activity and rotarod for motor coordination. Electrophysiological recordings were carried out in three major basal ganglia nuclei, the subthalamic nucleus (STN), globus pallidus (GP) and substantia nigra pars reticulata (SNr). At the end of experiments, post-mortem tissue level of the three monoamines (dopamine, noradrenaline and serotonin) and their metabolites has been determined using HPLC. Results: Lead intoxication significantly impaired exploratory and locomotor activity as well as motor coordination. It resulted in a significant reduction in the level of noradrenaline in the cortex and dopamine and its metabolites, DOPAC and HVA, in the striatum. The tissue level of serotonin and its metabolite 5-HIAA was not affected in the two structures. Similarly, DSP-4, which induced a selective depletion of noradrenaline, significantly decreased exploratory and locomotor activity as well as motor coordination. L-DOPA treatment did not improve motor deficits induced by lead and DSP-4 in the two animal groups. Electrophysiological recordings showed that both lead and DSP-4 did not change the firing rate but resulted in a switch from the regular normal firing to irregular and bursty discharge patterns of STN neurons. Neither lead nor DSP-4 treatments changed the firing rate and the pattern of GP and SNr neurons. Conclusions: Our findings provide evidence that lead represents a risk factor for inducing parkinsonism-like deficits. As the motor deficits induced by lead were not improved by L-Dopa, we suggest that the deficits may be due to the depletion of noradrenaline and the parallel disorganization of STN neuronal activity.